Taurine Supplementation Reduces the Oxidative Stress Associated with Galactosamine-Induced Fulminant Hepatic Failure in Rats - ASHA, K K; Devdasan, K (Fishery Technology, 2025)
The hepatoprotective effect of taurine on galactosamine (GalN)-induced hepatitis, an experimental model for fulminant hepatic failure was studied in Wistar strain male rats. Among the four groups of rats taken for the study, group one served as the control, group two rats were administered with taurine, group three rats were injected intraperitoneally with GalN to induce hepatitis and group four rats were administered with taurine prior to induction of hepatitis. The parameters studied were (i) the concentration of hepatic reduced glutathione (GSH); (ii) levels of hepatic thiobarbituric acid reactive substances (TBARS); (iii) the levels of hepatic antiperoxidative enzymes; (iv) the concentration of liver specific enzymes in serum; and (v) substantiating the biochemical findings by histopathological evidence. Both taurine administered and control rats showed similar values for all the parameters studied, indicating that taurine does not have any undesirable effect. A significant (p < 0.001) increase in the levels of enzymes in serum, and levels of TBARS in liver and decrease in the concentration of GSH and antiperoxidative enzymes in liver were observed in GalN-intoxicated rats. Prior treatment with taurine had negated the adverse effects of GalN-induced hepatitis as evidenced by decline in enzyme levels in serum and hepatic TBARS and the restoration of levels of GSH and antiperoxidative enzymes in liver. Liver histopathology shows that prior treatment with taurine protects liver from extensive hepatocellular necrosis caused by GalN intoxication. The present study revealed that administration of taurine reduces oxidative stress in hepatitisinduced rats, attenuates hepatic lipid peroxidation and protects GSH levels.